2022
DOI: 10.1101/2022.08.04.502828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA vaccines and hybrid immunity use different B cell germlines to neutralize Omicron BA.4 and BA.5

Abstract: SARS-CoV-2 omicron BA.4 and BA.5, characterized by high transmissibility and ability to escape natural and vaccine induced immunity, are rampaging worldwide. To understand the escape mechanisms, we tested the neutralizing activity against omicron BA.4 and BA.5 of a panel of 482 human monoclonal antibodies that had been isolated from people who received two or three mRNA vaccine doses or from people that had been vaccinated after infection. None of the antibodies isolated after two vaccine doses neutralized omi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Similarly, the N460K substitution that arose during the BA.2 to BA.2.75 transition conferred resistance to 6 class 1 or 1/4 antibodies with VH 3-53 and VH 3-66 heavy chains (Fig. 6c), that have previously been shown to generate antibodies that can neutralize BA.1 through BA.5 omicron variants 28 . Notably, the N460K substitution gave resistance to all 6 of the VH 3-53/VH 3-66 antibodies in the BA.2 background, but did not affect sensitivity to the same antibodies in the Wuhan-Hu-1 background (Fig.…”
Section: Epistatic Interactions For Mutations Selected In Vitro and N...mentioning
confidence: 92%
“…Similarly, the N460K substitution that arose during the BA.2 to BA.2.75 transition conferred resistance to 6 class 1 or 1/4 antibodies with VH 3-53 and VH 3-66 heavy chains (Fig. 6c), that have previously been shown to generate antibodies that can neutralize BA.1 through BA.5 omicron variants 28 . Notably, the N460K substitution gave resistance to all 6 of the VH 3-53/VH 3-66 antibodies in the BA.2 background, but did not affect sensitivity to the same antibodies in the Wuhan-Hu-1 background (Fig.…”
Section: Epistatic Interactions For Mutations Selected In Vitro and N...mentioning
confidence: 92%
“… n.a. GISAID name GRA (formerly GR/484 A) bamlanivimab (LY-CoV555 / LY3819253) ↓↓↓ ( Aggarwal et al, 2021 , Andreano et al, 2022 , Boschi et al, 2022 , Cao et al, 2021 , Gruell et al, 2021 , Hoffmann et al, 2021b , Iketani et al, 2022 , Liu et al, 2021 , Planas et al, 2021 , Sheward et al, 2021 , Tada et al, 2021a , Touret et al, 2022 , VanBlargan et al, 2022 , Zhou et al, 2022 ) ↓↓↓ ( Andreano et al, 2022 , Gruell et al, 2022 , Sheward et al, 2022a , Takashita et al, 2022a , Wang et al, 2022b , Yamasoba et al, 2022b ) (including BA.2.11, BA.2 L452Q, BA.2 S704L, BA.2 HV69-70del, BA.2 F486V, BA.2 R493Q ( Yamasoba et al, 2022b ) and BA.2.10.4 ( Sheward et al, 2022b )) ↓↓↓( Gruell et al, 2022 , Wang et al, 2022b , Yamasoba et al, 2022b ) ↓↓↓( Gruell et al, 2022 , Sheward et al, 2022a , Wang et al, 2022b , Yamasoba et al, 2022a ) ↓↓↓( Andreano et al, 2022 , Gruell et al, 2022 , Sheward et al, 2022a , Wang et al, 2022b , Yamasoba et al, 2022b ) ↓↓↓ ( Jian et al, 2022 , Sheward et al, 2022b ) ↓↓↓ ( Jian et al, 2022 ...…”
Section: Co-infections and Recombinantsmentioning
confidence: 99%
“…( Gruell et al, 2022 ) ↓↓↓( Yamasoba et al, 2022a ) ( Gruell et al, 2022 ) n.a. ( Gruell et al, 2022 ) - - - sotrovimab (VIR-7831 / GSK-4182136) (Xevudy®) ↓ ( Andreano et al, 2022 , Cao et al, 2021 , Gruell et al, 2021 , Hoffmann et al, 2021b , Ikemura et al, 2021 , Liu et al, 2021 , Planas et al, 2021 , Sheward et al, 2021 , Takashita et al, 2022b , Touret et al, 2022 , VanBlargan et al, 2022 ) (including BA.1.1 ( Takashita et al, 2022b )) ↓↓ ( Aggarwal et al, 2022 , Andreano et al, 2022 , Gruell et al, 2022 , Iketani et al, 2022 , Ohashi et al, 2022 , Sheward et al, 2022a , Takashita et al, 2022a , Takashita et al, 2022b , Wang et al, 2022b , Yamasoba et al, 2022b , Zhou et al, 2022 ) (including BA.2.11, BA.2 L452Q, BA.2 S704L, BA.2 HV69-70del, BA.2 F486V, BA.2 R493Q ( Yamasoba et al, 2022b ) and BA.2.10.4 ( Sheward et al, 2022b )) ↓↓ ( Gruell et al, 2022 , Takashita et al, 2022b , Wang et al, 2022b , Yamasoba et al, 2022b ) ↓↓↓( Gruell et al, 2022 , Wang et al, 2022b , Yamasoba et al, 2022a ) BA.2.75.2: ↓↓↓ ( Sheward et al, 2022b ) ↓↓( …”
Section: Co-infections and Recombinantsmentioning
confidence: 99%
“…SARS-CoV-2 exhibits high infectivity capacity and has reached millions of cases worldwide, with millions of deaths observed [ 16 , 37 , 38 ]. Brazil has faced a rapid escalation of COVID-19 cases and almost seven hundred thousand registered deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil has faced a rapid escalation of COVID-19 cases and almost seven hundred thousand registered deaths. Despite the reduction in the number of cases and deaths in Brazil, new waves could emerge at any time, considering the emergence of new SARS-CoV-2 super spreading variants that may escape from the immune response or the available vaccines or drugs [ 10 , 37 , 38 , 39 , 40 ]. Several studies have reported the antibody response profile to SARS-CoV-2, which includes the broad clinical and vaccinology spectrum of COVID-19, however, many aspects of the humoral immune response in COVID-19 remain obscure in both situations [ 17 , 21 , 29 , 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%